Utilising Response Surface Methodology to Optimise Food Additives and Treatments Reduces Disease Caused by Penicillium digitatum and Penicillium italicum in ‘Valencia’ Oranges - Archer, John; Pristijono, Penta; Vuong, Quan V.; Palou, Lluís; Golding, John B. (MDPI, 2024)
Penicillium digitatum and Penicillium italicum are responsible for citrus green and blue moulds (GM and BM), respectively, which are major citrus postharvest diseases. The aim of this study was to develop an optimal dipping mixture of an aqueous solution of different food additives: sodium bicarbonate (SB), sodium benzoate (SBen), and potassium sorbate (PS), in combination with heat, to control GM and BM using response surface methodology. The ranges of SB (0.0%, 3.0%, 6.0%), SBen (0.0%, 0.5%, 1.0%), PS (0.0%, 0.5%, 1.0%) and temperature (20 ◦C, 35 ◦C, 50 ◦C) with a dipping time of 60s were tested for their impact on GM and BM on artificially inoculated oranges. Within these tested ranges, SB reduced GM severity and incidences of both GM and BM. PS affected BM severity and incidence, but not GM. SBen and temperature did not have impact on GM and BM. The most suitable food additive concentrations were identified to be 4.7% SB, 1.0% SBen and 0.7% PS, with a dipping solution temperature of 50 ◦C. This treatment was shown to reduce GM and BM incidence from 85 and 86% on control fruit dipped in tap water at 20 ◦C to 3 and 10%, respectively. Additionally, the severity of GM and BM was reduced from 64 and 26 mm on control fruit to <1 and 2.8 mm, respectively.